Fiber Optic Installer's Field Manual - Chomycz, Bob. (New York : McGraw-Hill Education, 2015)
"A fully updated fiber optic cable installation guideExtensively revised to cover the latest technologiesand equipment, this portable tool shows you how toplan, install, and maintain a robust fiber optic networkto support today's high speed requirements. The emphasis is on practical, efficient installation techniques using current global industry standards. Detailed diagrams and step-by-step procedures walk you through the entire process. This completely up-to-date edition is an essential on-the-job reference.Fiber Optic Installer's Field Manual, Second Edition, covers: Properties of light Optical fiber Fiber optic cables Fiber optic cable procurement Safety precautions Handling fiber optic cable Outdoor fiber optic cable installation Indoor cable installation Fiber optic cable general installation guide Splicing and termination Patch cords and connectors Optical fiber power loss and measurement The OTDR and OSA Fiber optic installation tests Transceivers such as SFP and XFP WDM and other passive optical equipment SONET/SDH Ethernet over fiber Fiber system deployment Maintenance Emergency cable repair Network documentation Troubleshooting Design fundamentals Personnel Dark fiber leasing Global standards reference tables "--
Machine generated contents note: Ch. 1 Introduction Ch.2 Properties of Light Ch. 3 Optical Fiber Ch. 4 Fiber Optic Cables Ch. 5 Cable Procurement Ch. 6 Safety Precautions Ch. 7 Handling Fiber Optic Cable Ch. 8 Outdoor Cable Installation Ch. 9 Indoor Cable Installation Ch. 10 Fiber Optic Cable General Installation GuidelineCh. 11 Splicing and Termination Ch. 12 Patch Cords and Connectors Ch. 13 Power Meter, Source and Return Loss Measurement Ch. 14 The OTDR and OSACh. 15 Fiber Characterization (Loss, CD, PMD, ORL, Latency)Ch. 16 Fiber Optic Installation Tests Ch. 17 Lightwave Equipment Ch. 18 Wavelength Division MultiplexersCh. 19 Other Fiber ComponentsCh. 20 SONET/SDHCh. 21 LANCh. 22 Fiber System DeploymentCh. 23 Maintenance Ch. 24 Emergency Cable Repair Ch. 25 Records Ch. 26 Troubleshooting Ch. 27 Design Fundamentals Ch. 28 Personnel Ch. 29 Dark Fiber LeasingAppendices[bullet] Glossary of Terms and Acronyms[bullet] Units[bullet] Optical Fiber Color Codes[bullet] Fiber Optic Records[bullet] Relevant Standards and References[bullet] Transceiver Standards and Naming Convention[bullet] DWDM 100GHz and 50GHz Channel SpacingIndex.
Includes bibliographical references and index.
Keywords: Fiber optics -- Equipment and supplies -- Installation -- Handbooks, manuals, etc; Optical communications -- Equipment and supplies -- Installation -- Handbooks, manuals, etc; Optical communications -- Fieldwork -- Handbooks, manuals, etc; Technology & Engineering / Fiber Optics